Implementasi Rumah Generasi Emas (RGE) di Desa Jatiluhur Kabupaten Purwakarta - Nur Azizah; Gartika Dwi Jayanti; Tiara Dewi Lestari; Shinta Nadiha Wardani (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2022)
In designing the vision of Indonesia Emas 2045, it is supported by 4 pillars, one of which is superior Indonesian people, cultured and mastering science and technology. However, the community's readiness to face Indonesia Emas 2045 is still lacking, especially for people in the village environment. Village communities have difficulty accessing education. In this article, the author describes Rumah Generasi Emas which was initiated as a solution to fulfill access to education for children in Jatiluhur Village. The results showed that RGE has 2 service locations, RT 14 and RT 08 Jatiluhur Village, Purwakarta Regency. The children seemed very enthusiastic about participating in the activities at RGE. This is evidenced by the large number of children who take part in the RGE at each meeting. In addition, RGE is also supported by the head of Jatiluhur Village, parents of children in RT 14 and RT 08, and Purwakarta regional central library. RGE has 3 main programs that are taught to children, namely an educational film screening program, a foreign language training program, and a skills program. Educational film screening programs allow children to get positive values. Foreign language training programs, the gates of knowledge are increasingly wide open. The skills program allows children to express themselves and be able to hone their artistic aspects of children. All of these programs are run by RGE to support the achievement of Indonesia Emas 2045.